Current ideas about pathogenesis and treatment of so-called essential epilepsy (Concluded) - Bambaren, Carlos A. (1920)
Epilepsy is not a unique disease entity, as once he believed. The breakup initiated by Bravais and JACKSON, and continued progress that has been made in the domain of the causes of seizure processes has called essential epilepsy disappeared, to become well qualified all cases symptomatic. No epilepsy but epilepsies. In cases of essential epilepsy titled The analysis finds descriminativo pathogenetic factors, which must be accepted as the cause of pathic state, because clinical observation, the data provided by modern methods of etiological research and therapy, attend together to try their performance morbígena.